2019
DOI: 10.3390/agriculture9110233
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of UAV Photogrammetry and 3D Modeling Techniques with Other Currently Used Methods for Estimation of the Tree Row Volume of a Super-High-Density Olive Orchard

Abstract: A comparison of three different methods to evaluate the tree row volume (TRV) of a super-high-density olive orchard is presented in this article. The purpose was to validate the suitability of unmanned aerial vehicle (UAV) photogrammetry and 3D modeling techniques with respect to manual and traditional methods of TRV detection. The use of UAV photogrammetry can reduce the amount of estimated biomass and, therefore, reduce the volume of pesticides to be used in the field by means of more accurate prescription m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 27 publications
3
40
0
Order By: Relevance
“…Mesas-Carrascosa et al [19] reported good results comparing ground measurements of the heights of individual grapevines with the estimated heights from the UAV point cloud, showing high determination coefficients (R 2 > 0.87) and low root-mean-square error (0.07 m). For volume characterization, Anifantis et al [2] described the calculation of tree row volume (TRV) comparing three different methodologies that show an average value of the difference equal to +13% between the method based on UAV and manual in situ measurements. Caruso et al, 2017 found a good correlation between measured and UAV estimated canopy volume, with a constant height of 0.9 m R 2 was equal to 0.62, while R 2 increased (0.75) when the actual distance of the canopy from the ground was used in the calculation, but in this case the estimated canopy volume diverged from the 1:1 line.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mesas-Carrascosa et al [19] reported good results comparing ground measurements of the heights of individual grapevines with the estimated heights from the UAV point cloud, showing high determination coefficients (R 2 > 0.87) and low root-mean-square error (0.07 m). For volume characterization, Anifantis et al [2] described the calculation of tree row volume (TRV) comparing three different methodologies that show an average value of the difference equal to +13% between the method based on UAV and manual in situ measurements. Caruso et al, 2017 found a good correlation between measured and UAV estimated canopy volume, with a constant height of 0.9 m R 2 was equal to 0.62, while R 2 increased (0.75) when the actual distance of the canopy from the ground was used in the calculation, but in this case the estimated canopy volume diverged from the 1:1 line.…”
Section: Discussionmentioning
confidence: 99%
“…Anifantis et al [2] performed a comparison on an adult super-high-density olive orchard, using three methods for tree row volume (TRV). The first method (TRV1) was based on close-range photogrammetry from UAVs, the second (TRV2) was based on manual in situ measurements, and the third (TRV3) was based on a formula from the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Sugar beet is an extensive crop of great agronomic value with significant productive and economic returns; moreover, it has always been considered an "improvement crop" from which all crops in succession benefit [3][4][5][6]. Sugar beet and the by-products resulting from its industrial transformation are a noteworthy renewable energy resource [7][8][9][10], e.g., pulps can be used in biogas and electricity production [11][12][13][14][15], and beet leaves and tops are currently used as a fundamental component in the food rations of animal farms, as they are rich in nutrients and they can be employed as a substrate in anaerobic digestion for renewable energy production, due to the high content of both sugar and almost completely digestible fibers [16,17]. Furthermore, large amounts of the sugar industry's different kinds of generated waste, such as sugar beet pulp and leaves, can be employed as precious substrates in the production of biotechnology cellular proteins, enzymes, organic acids, etc.…”
Section: Introductionmentioning
confidence: 99%
“…and of the tractors that tow these implements (power; measurements, etc.) [24][25][26]. Therefore, each operational unit analysed the crops grown in its own reference area.…”
Section: Introductionmentioning
confidence: 99%